A phase III study evaluating oral glutamine and transforming growth factor-beta 2 on chemotherapy-induced toxicity in patients with digestive neoplasm. Issue 3 (March 2016) - Khemissa, Faïza; Mineur, Laurent; Amsellem, Caroline; Assenat, Eric; Ramdani, Mohamed; Bachmann, Patrick; Janiszewski, Chloé; Cristiani, Isabelle; Collin, Fideline; Courraud, Julie; de Forges, Hélène; Dechelotte, Pierre; et al.
Abstract: Background: Patients with gastrointestinal (GI) cancer are exposed to cachexia, which is highly correlated with chemotherapy-induced side effects. Research suggests that specific immunonutrients could prevent such toxicities. Aims: The primary objective of this phase III study was to evaluate the efficacy of glutamine and transforming growth factor-β2 (TGF-β2) in the prevention of grade 3–4 non-hematological toxicities induced by chemotherapy in patients with GI cancer. Patients and methods: We designed a double-blind, randomized, controlled and multicenter trial stratified according to center, type of chemotherapy, presence of cachexia, and age. Patients were randomized to receive either Clinutren Protect ® (CP) or a control isocaloric diet (without TGF-β2 or glutamine). Results: Between November 2007 and October 2011, 210 patients were enrolled in the study, of which 201 were included in the intention-to-treat analysis. Grade 3–4 non-hematological toxicities were not significantly different between the CP and control groups when evaluated by univariate and multivariate analyses. Likewise, no difference was observed regarding grade 3–4 hematological toxicities or reasons for treatment interruption. Conclusion: This randomized study does not support the hypothesis that oral glutamine and TGF-β2 supplementation is effective to reduce grade 3 or 4 non-hematological toxicities induced by chemotherapy in patients with GI neoplasm.